Weight Gain, Metabolic Syndrome, and Breast Cancer Recurrence: Are Dietary Recommendations Supported by the Data?. (24th September 2012) - Champ, Colin E.; Volek, Jeff S.; Siglin, Joshua; Jin, Lianjin; Simone, Nicole L.
Abstract : Metabolic syndrome, which can include weight gain and central obesity, elevated serum insulin and glucose, and insulin resistance, has been strongly associated with breast cancer recurrence and worse outcomes after treatment. Epidemiologic and prospective data do not show conclusive evidence as to which dietary factors may be responsible for these results. Current strategies employ low-fat diets which emphasize supplementing calories with increased intake of fruit, grain, and vegetable carbohydrate sources. Although results thus far have been inconclusive, recent randomized trials employing markedly different dietary strategies in noncancer patients may hold the key to reducing multiple risk factors in metabolic syndrome simultaneously which may prove to increase the long-term outcome of breast cancer patients and decrease recurrences. Since weight gain after breast cancer treatment confers a poor prognosis and may increase recurrence rates, large-scale randomized trials are needed to evaluate appropriate dietary interventions for our breast cancer patients.